Fracture properties of green mortars with recycled sand - Luciana Restuccia (Fracture and Structural Integrity, 2019)
Urbanisation is consuming huge amounts of sand, being the basic element of concrete and glass, two of the most popular construction materials. Unfortunately, sand mining is causing environmental damage and drastically reducing the amount of raw resources. The main topic of this research is to investigate the use of Construction and Demolition waste finer fraction - namely recycled sand - to totally replace the standard one into traditional mortars. From the analysis of the mechanical characterization of specimens, it is possible to state that recycled sand could represent a new resource for green and sustainable mortars.